Tekutinová bilance a akutní poškození ledvin: důvod k zamyšlení - Bouchard, Josee; Soroko, Sharon B; Chertow, Glenn M; Himmelfarb, Jonathan; Ikizler, T. Alp; Paganini, Emil P; Mehta, Ravindra L (Postgraduální nefrologie, 2009)
Fluid accumulation is associated with adverse outcomes in critically ill patients. Here, we sought to determine if fluid accumulation is associated with mortality and non-recovery of kidney function in critically ill adults with acute kidney injury. Fluid overload was defined as more than a 10% increase in body weight relative to baseline, measured in 618 patients enrolled in a prospective multicenter observational study. Patients with fluid overload experienced significantly higher mortality within 60 days of enrollment. Among dialyzed patients, survivors had significantly lower fluid accumulation when dialysis was initiated compared to non-survivors after adjustments for dialysis modality and severity score. The adjusted odds ratio for death associated with fluid overload at dialysis initiation was 2.07. In non-dialyzed patients, survivors had significantly less fluid accumulation at the peak of their serum creatinine. Fluid overload at the time of diagnosis of acute kidney injury was not associated with recovery of kidney function. However, patients with fluid overload when their serum creatinine reached its peak were significantly less likely to recover kidney function. Our study shows that in patients with acute kidney injury, fluid overload was independently associated with mortality. Whether the fluid overload was the result of a more severe renal failure or it contributed to its cause will require clinical trials in which the role of fluid administration to such patients is directly tested.
Keywords: Body Fluids; Body Weight; obnova funkce; vodní a elektrolytová rovnováha; Water-Electrolyte Balance; lidé středního věku; Critical Illness; Survival Rate; lidé; Middle Aged; Prospective Studies; prospektivní studie; Edema; Acute Kidney Injury; Female; financování organizované; odds ratio; tělesné tekutiny; Male; ženské pohlaví; Humans; mužské pohlaví; edém; akutní poškození ledvin; Financing, Organized; míra přežití; Recovery of Function; Odds Ratio; tělesná hmotnost; kritický stav